2022
DOI: 10.37934/araset.28.3.376392
|View full text |Cite
|
Sign up to set email alerts
|

Simulation on Building Envelope Design using Biomimicry Conceptual of Palm Leaf Pattern for Self Cleaning Maintenance

Abstract: Contemporary architectural designs acting to increase the aesthetic value of the building’s overall perspective. The complexity of the maintenance works for the building envelope cleanliness becomes challenging in maintenance operations. Biomimicry – innovation inspired by nature, reveals an opportunity to simplify the cleaning process mentioned by infusing the self-cleaning characteristic of palm tree species on the design of building envelope. This research is intentionally to determine of the most ideal bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…A structure's facade is its outward appearance and, as such, greatly affects how people view the building [1][2]. Due to its role in controlling the amount of heat from the daylight and providing daylight, ventilation, and sun shading [3][4], the façade's form becomes quite important in conserving energy. Romano et al, [5] found that a comprehensive analysis of a building's behaviour reveals that the ability to bend rather than break under a sudden force is preferable.…”
Section: Introductionmentioning
confidence: 99%
“…A structure's facade is its outward appearance and, as such, greatly affects how people view the building [1][2]. Due to its role in controlling the amount of heat from the daylight and providing daylight, ventilation, and sun shading [3][4], the façade's form becomes quite important in conserving energy. Romano et al, [5] found that a comprehensive analysis of a building's behaviour reveals that the ability to bend rather than break under a sudden force is preferable.…”
Section: Introductionmentioning
confidence: 99%